Design of a Human Machine Interface for Programming and Testing Adjustable Frequency Drives for Constant Pressure Pumping Applications - Remache-Vinueza, Byron (2021)
In this project, a human machine interface (HMI) was developed for programming adjustable frequency drives (AFDs). Frequency drives have a wide range of industrial applications such as pumping systems, conveyor belts, ventilation and air conditioning systems, and, in general, applications that require motors with high torque. Constant pressure pumping systems with AFDs, for instance, allow working with a proportional integral derivative (PID) control, providing the system with precise response between the desired value and the process feedback. In this project, an HMI has been designed to effectively configure, test and calibrate AFDs for constant pressure pumping applications. Various alternatives of HMI screens were analyzed using the prioritization matrix method to determine the most suitable screen. The HMI interface was developed in the DOPsoft 4 software of DELTA Electronics, following the guidelines set forth by ANSI/ISA-101.01-2015, to generate a clear and easy to understand HMI.